Model of Relationships Among Marketing Public Relations, Service Quality and Attitude Toward Brand - Trinh, Viet Dung; Nguyen, Hoang Mai (ASEAN Marketing Journal, 2021)
Manuscript type: Full research paper. Research Aims: Exploratory. Design/methodology/approach: This research is based on quantitative data collected from 317 respondents who took part in various MPR programs of RMIT International University Vietnam (RMIT Vietnam) in 2016. Research Findings: Through multiple regression analysis, it was concluded that MPR has a positive relationship with ATB and the tangibles dimension of SERVQUAL; MPR also indirectly affects ATB through this service quality dimension. This research concluded with a model of the relationships among MPR, service quality and ATB. Theoretical Contribution/Originality: This research is based on the perspective that public relations may have significant value in terms of marketing, and MPR could benefit corporates by enhancing their services as well as long-term relationships with and trust of customers by generating a positive attitude toward their brand. Research limitation/Implications: For the implementations, managers of RMIT Vietnam are highly recommend to make the MPR programs more tangible to gain positive ATB. Other service providers will enhance their service quality and adjust the budget accordingly by implementing this model for innovative solutions to ongoing marketing programs.